The Dialectics of Godhead in Judaism, Christianity, and Islam: Philosophical and Historical Perspectives - Amirudin, Amirudin; Kulkarni, Heramb; Al Ghozali, Muhammad Iqbal; Karim, Abdul (Universitas Islam Negeri Madura, 2024)
The issue of Godhead is a principal ideological problem, so historical-theological and philosophical studies are necessary to clarify scientific positions to strengthen arguments. The study in this paper is an attempt to trace the three Samawi religions (Abrahamic religions), which in its findings, it turns out that several conclusions have basic similarities. This paper is the result of qualitative research with literature studies from various literature to reveal historical problems that try to reduce unilateral claims based on the theological tendencies of each religion. With a historical-philosophical approach, the author attempts to provide descriptions and arguments regarding the fusion of human belief systems. The findings obtained in this paper are to understand the ideological-historical aspect, where it turns out that among Samawi religions, there is an evolution of belief systems in God. Then, they are used as theological and ideological systems.